School leadership and education system reform - Earley, Peter; Greany, Toby (London Bloomsbury Academic, 2017)
"Critically considers education system reform and its relationship to school leadership and learning in the global context, including school autonomy and accountability in 'self-improving systems'"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Educational leadership -- Great Britain; School management and organization -- Great Britain; School improvement programs -- Great Britain